Studies in symbolic interaction. - Denzin, Norman K.; Salvo, James (JAI, 2004)
Volume 27 of "Studies in Symbolic Interaction" emphasizes new developments in interactional theory and practice, as well as examples of post-modern ethnography and performance texts focused on border crossings and border performances. The volume also presents essays honoring Laurel Richardsons contributions to Symbolic Interaction and Communications, as well as the inaugural address in the "Peter M. Hall Lecture Series".